Урожайність сортів нуту залежно від удобрення в Степу України - Чумак, Іван Сергійович; Chumak, Ivan (ЦНТУ, 2024)
В даній кваліфікаційній роботі вивчено вплив удобрення на продуктивність нуту. Мета досліджень – вивчити оптимальне дозу удобрення для посівів нуту. Встановлено, що застосування удобрення позитивно відображається на онтогенезі нуту та сприяє підвищенню його урожайності в умовах Степу України. In this qualification work, the influence of fertilizer on chickpea productivity was studied. The purpose of research is to study the optimal dose of fertilizer for chickpea crops. It has been established that the use of fertilizer has a positive effect on the ontogenesis of chickpeas and helps to increase its productivity in the conditions of the Steppe of Ukraine.
Yields of chickpea varieties depending on fertiliser in the Steppe of Ukraine
Keywords: нут; удобрення; врожайність; chickpea; fertiliser; yield